ETOS KERJA ORANG SUNDA MENURUT PERSPEKTIF FILSAFAT ESSENSIALISME - Afif, Deyaha (STKIP PGRI SUMENEP, 2024)
This study aims to reveal the meaning of work ethic contained in local wisdom, namely in the terms of Sundanese paribasa by describing and interpreting the content of Sundanese paribasa which contains the values of the work ethic of the Sundanese through the perspective of the philosophy of the essensialism school. This research uses qualitative descriptive research methods with data acquisition methods through literature riview, field observation, and documentation. The object of this study is the term paribasa Sunda which contains the values of the work ethic of the Sundanese people which until now is still actively used in the community. The result of this study show that there are as many as 11 paribasa that are still actively used by the Sundanese community and have work ethic values, including, namely (1) Kudu bisa ngeureut neundeun/pakéan, (2) Bibilintik ti leuleutik babanda ti bubudak, geus gedé ngan kari maké, (3) Mun teu ngarah moal ngarih, mun teu ngakal moal ngakeul, mun teu ngoprék moal nyapék, (4) Kudu bisa ngeureut neundeun saeutik mahi loba nyésa, (5) Kudu nété tarajé nincak hambalan, (6) Ari diarah supana, kudu dijaga catangna, (7) Ayakan tara meunang kancra, (8) Bengkung ngariung bongkok ngaronyok, (9) Cikaracak ninggang batu, laun-laun jadi legok, (10) Cul dogdog tinggal igel, (11) Élmu tungtut dunya siar, sukan-sukan sakadarna. Paribasa-paribasa it belongs to the type of paribasa pangjurung laku hadé. Keywords: work ethic, philosophy, essentialism, Sundanese paribasa